1985
DOI: 10.1161/01.hyp.7.6_pt_2.ii135
|View full text |Cite
|
Sign up to set email alerts
|

Abnormalities of platelet function in hypertension and diabetes.

Abstract: SUMMARY The increased frequency of hypertension in diabetes and of abnormalities of carbohydrate metabolism in hypertension are now well established. It is conceivable that the high coincidence of the two diseases is based on a common metabolic defect. Studies of platelets permit the evaluation of the stimulatory, phospholnositol-linked and the inhibitory, cyclic adenosine 3',5'-monophosphatedependent pathways of cell activation. Furthermore, platelets may be relevant for the development of angiopathy through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
27
1

Year Published

1989
1989
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 29 publications
(17 reference statements)
4
27
1
Order By: Relevance
“…23 In addition, these hypofunctions were demonstrated with any of the platelet preparations 28 (whole blood, platelet rich plasma, gel-filtered, and washed) and also with various aggregating agents. 1 The results obtained by Hamet et al 33 coincides well with ours. In contrast, Koutouzov et al 34 and Huzoor-Akbar and Anwer 35 have reported increased aggregation in platelets of SHR.…”
Section: Effect Of 12-o-tetradecanoylphorbol 13-acetate and Ca Ionophsupporting
confidence: 84%
See 1 more Smart Citation
“…23 In addition, these hypofunctions were demonstrated with any of the platelet preparations 28 (whole blood, platelet rich plasma, gel-filtered, and washed) and also with various aggregating agents. 1 The results obtained by Hamet et al 33 coincides well with ours. In contrast, Koutouzov et al 34 and Huzoor-Akbar and Anwer 35 have reported increased aggregation in platelets of SHR.…”
Section: Effect Of 12-o-tetradecanoylphorbol 13-acetate and Ca Ionophsupporting
confidence: 84%
“…In this paper the mechanism of the defective protein phosphorylation related to hypoaggregability was investigated. In 1988, HuzoorAkbar and Anwer 33 reported an increase in thrombininduced protein phosphorylation, and Koutouzov et al 34 observed an increase in phospholipase C activity in thrombin-stimulated platelets of SHR. These results contradict ours that were obtained in platelets of SHRSP.…”
Section: Camentioning
confidence: 99%
“…One proposed function is that it contributes to the modulation of cyclic nucleotide signaling by reducing intracellular levels of these second messengers. In support of this notion is the consistent observation that triggered elevations in intracellular cyclic nucleotide levels are associated with enhanced cellular efflux (52)(53)(54)(55)57). A second proposed function for efflux is in provision of extracellular cAMP involved in intercellular signaling.…”
Section: Discussionmentioning
confidence: 79%
“…Triglyceride-rich lipoproteins in the vessel wall and associated cells (23) lead to fatty streaks, which are noted in saphenous vein grafts within 18 months post-CABG (24). An enhanced blood coagulation-fibrinolytic system may be associated with both serum triglyceride concentrations (25) and the presence of diabetes (5,26). In the postmenopausal period (the typical life-cycle phase for women in this study), hepatic lipase activity rises because of an absence of estrogen, leading to an increase in small dense LDLs (27), particularly observed in the presence of a high concentration of triglyceride particles (28).…”
Section: Sprecher and Associatesmentioning
confidence: 99%